2015
DOI: 10.1038/srep10113
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Time on Task in Response Selection - An ERP Study of Mental Fatigue

Abstract: Long lasting involvement in a cognitive task leads to mental fatigue. Substantial efforts have been undertaken to understand this phenomenon. However, it has been demonstrated that some changes with time on task are not only related to mental fatigue. The present study intends to clarify these effects of time on task unrelated to mental fatigue on response selection processes at the behavioural and electrophysiological level (using event-related potentials, ERPs). Participants had to perform a Simon task for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 39 publications
(47 reference statements)
2
98
0
2
Order By: Relevance
“…In contrast, mental fatigue resulted in greater stability of the distances between players within the same team but with lower levels of between-player synchrony. A possible explanation for these observations is that mental fatigue impairs players' perception of available information and also might affect their ability to identify suitable possibilities for action (Boksem et al, 2006;Coutinho et al, 2017;Nedelec et al, 2012;Smith, Zeuwts, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, mental fatigue resulted in greater stability of the distances between players within the same team but with lower levels of between-player synchrony. A possible explanation for these observations is that mental fatigue impairs players' perception of available information and also might affect their ability to identify suitable possibilities for action (Boksem et al, 2006;Coutinho et al, 2017;Nedelec et al, 2012;Smith, Zeuwts, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, other markers should be used in complement to confirm this assessment, such as the frontal theta waves which can be assessed with an electroencephalogram test (Wascher et al, 2014). The level of motivation of the players could also have been monitored, as it has been shown that motivation may impact more the performance than the mental fatigue in longer lasting exercise protocols (Mockel, Beste, & Wascher, 2015;Wascher et al, 2014). It is possible that the performance measures in the present study might have been influenced by reduced player motivation in the final test conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mockel et al [12] studied the effect of mental fatigue on ERPs. They asked subjects to perform a Simon task [13] for more than three hours and investigated variations of mental fatigue and motivation.…”
Section: Introductionmentioning
confidence: 99%